L-Methylfolate in Antidepressant Non-responders: The Impact of Body Weight and Inflammation - Macaluso, Matthew (Frontiers in Psychiatry, 2022)
The objective of this summary is to provide context for the role of L-methylfolate (LMF) in treating antidepressant non-responders. Bidirectional relationships have been observed between obesity/inflammation and depression. Studies have shown an increased prevalence of depression among patients with elevated body mass index and/or chronic inflammation, and an increased risk for becoming obese and experiencing chronic inflammation in those with depression. These relationships can negatively affect the pathophysiology of depression. Increased cytokine levels can reduce neurotransmitter concentrations, which has been associated with depressive symptoms. Reduced neurotransmitter levels (e.g., serotonin) can hinder the effectiveness of commonly used antidepressant therapies, such as selective serotonin reuptake inhibitors (SSRIs). LMF is an approved nutritional adjunctive antidepressant therapy that can increase central neurotransmitter levels and thereby improve the effectiveness of antidepressant therapy. LMF can increase clinical response when used adjunctively in patients with major depressive disorder (MDD) not responding to an adequate SSRI trial. In randomized controlled trials, when LMF is added to an SSRI increased response rates (32.3% vs 14.6%; P=0.04) as measured by the Hamilton Depression Rating Scale (HAM-D) and produced greater mean HAM-D reductions(−5.6 vs −3.0; P=0.05) compared to an SSRI plus placebo. Additionally, LMF has demonstrated effectiveness in real-world studies, with 67.9% of patients responding to therapy, using the 9-item Patient Health Questionnaire (P<0.001). Post hoc analyses found that patients with inflammation and/or obesity responded better to adjunctive LMF therapy when compared to the overall sample (mean HAM-D reduction: −2.74 vs +0.99).